Three essays on financial self-efficacy beliefs and the saving behavior of older pre-retirees - Asebedo, Sarah D. (Kansas State University, 2016)
This dissertation employed a psychological framework to investigate the saving behavior of older pre-retirees through three essays using data from the Health and Retirement Study (HRS). Understanding the connection between psychological characteristics and saving behavior is critical as this population attempts to bridge the retirement saving gap. Of these characteristics, financial self-efficacy beliefs (FSE) are theoretically vital to saving behavior. With the FSE beliefs of older adults weak and vulnerable to decline, more research is needed to understand how FSE beliefs affect saving behavior and how FSE beliefs can be supported. Essay one investigated the psychological characteristics associated with FSE beliefs according to the Meta-Theoretic Model of Motivation and Personality (3M). Using a sample of 2,070 pre-retirees aged 50 to 70, essay one revealed that FSE beliefs can be supported through the frequent experience of positive affect, reduced negative affect, a stronger perception of mastery, and a higher task orientation, holding all else constant. Essay two investigated the relationship between FSE beliefs and saving behavior (i.e., change in net worth from 2008 to 2012) through the Social Cognitive Theory of Self-Regulation. Using a sample of 844 pre-retirees aged 50 to 70, results revealed that FSE beliefs are significantly and positively related to saving behavior, after controlling for the financial ability and motivation to save. Essay three employed a structural equation model to investigate an integrated psychological approach to saving behavior based upon the 3M. Using a sample of 1,370 pre-retired and partially retired adults aged 50 to 70, essay three revealed that FSE beliefs facilitated the connection between elemental traits (i.e., openness, conscientiousness, extroversion, agreeableness, and neuroticism), compound traits (i.e., positive affect, negative affect, mastery, and task orientation), and saving behavior. Overall, significant evidence was generated supporting a psychological approach to the saving behavior of older pre-retirees. Financial and mental health professionals can utilize this framework to provide holistic retirement saving advice that acknowledges the psychological roots of behavior. Moreover, results established empirical support for the role FSE beliefs play in executing saving behavior. Lastly, results supported the importance of domain specific measurement for self-efficacy beliefs in future research.
Keywords: Saving behavior; Financial self-efficacy; Older pre-retirees; Psychology; 3M model of motivation and personality; Social cognitive theory of self-regulation